2022
DOI: 10.3346/jkms.2022.37.e107
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Tuberculosis in Patients With Inflammatory Bowel Disease Treated With Vedolizumab or Ustekinumab in Korea

Abstract: The present study investigated the risk of active tuberculosis in patients with inflammatory bowel disease (IBD) treated with vedolizumab or ustekinumab, in actual clinical settings in a country with an intermediate tuberculosis burden. The medical records of 238 patients with IBD who received vedolizumab or ustekinumab were retrospectively reviewed at a tertiary referral center in South Korea. All patients had ≥ 3 months of follow-up duration and underwent a latent tuberculosis infection screening test before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
(20 reference statements)
1
8
0
1
Order By: Relevance
“…[ 17 ] Furthermore, a retrospective study of patients with IBD with latent TB infection who received VDZ revealed no cases of active TB infection. [ 18 20 ] Choi et al reported a case of a pediatric patient with CD who successfully achieved and maintained remission with VDZ after developing pulmonary TB during infliximab treatment. This case report is very similar to the present case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 17 ] Furthermore, a retrospective study of patients with IBD with latent TB infection who received VDZ revealed no cases of active TB infection. [ 18 20 ] Choi et al reported a case of a pediatric patient with CD who successfully achieved and maintained remission with VDZ after developing pulmonary TB during infliximab treatment. This case report is very similar to the present case.…”
Section: Discussionmentioning
confidence: 99%
“…Three developed latent TB infection Bonovas et al (2016) [16] Meta-analysis N/A 461 Odds ratio of TB numerically higher with VDZ vs placebo (2.50, 95% CT, 0.06-104.43). Result did not reach statistical significance Amiot et al (2016) [17] Prospective observation study France 294 One patient developed TB infection (0.34%) despite a negative pretherapeutic screening Ramos et al (2018) [18] Retrospective study of IBD patients who received biologic with LTBI USA 7 None developed active TB infection (0%) in 7 patients treated with VDZ Kim et al (2021) [19] Retrospective study of IBD patients who developed LTBI Korea 47 Positive IGRA conversion was observed in 4 patients (8.5%), none of the 4 converters developed active TB infection Choi et al (2022) [20] Retrospective study (real world data) Korea 125 None developed active TB infection (0%) in patients treated with VDZ Choi et al (2021) [21] Case report Korea VDZ is a humanized monoclonal antibody that selectively binds to the α 4 β 7 integrin. VDZ inhibits lymphocyte adhesion to mucosal addressin cell adhesion molecule-1 and subsequent migration.…”
Section: Publicationmentioning
confidence: 99%
“…39 Relatively, other biologics such as ustekinumab and vedolizumab, have lower rates of latent tuberculosis reactivation. 40 Tuberculosis infection can be disseminated and fatal. 36 Therefore, with the high popularity of anti-TNF agents in East Asia, reactivation of latent tuberculosis is a main concern before biologics initiation.…”
Section: High Prevalence Of Opportunistic Infectionsmentioning
confidence: 99%
“…M. Choi и соавт. предлагают рассматривать эти препараты в качестве оптимального выбора для больных с ВЗК в странах, где бремя ТБ является значительным [17].…”
Section: клинические наблюденияunclassified